Regret in One-Shot and Recurrent Decisions: A Cautionary Tale - Alex Imas; Diego Lamé; Alistair J. Wilson (Center for Economic Studies and ifo Institute (CESifo), 2016)
Under regret theory, decision-makers derive utility both from the outcome of their chosen action and the counterfactual. Evidence for anticipatory regret aversion has been found in oneshot settings, with ”regret lotteries” that always reveal outcomes, as a counterfactual on non-entry, being priced higher than comparable standard lotteries that only realize outcomes for entrants. However, as anticipation and realization of regret necessarily interact in dynamic settings, the predictions of regret theory for repeated decisions are far from clear. Indeed while our one-shot experimental data corroborate the previous findings, data from a sequence of decisions show the reverse, with regret lotteries priced lower than standard lotteries and their certainty equivalents. Given the recent literature on the use of regret lotteries as incentives, our results suggest that while these lotteries can be effective for motivating one-time decisions, their benefits as a repeated incentive is less than clear. More generally, the paper illustrates the issues that can arise when extrapolating behavioral effects from one-shot to recurrent settings.
Keywords: 330; regret aversion; separability; incentives